2007
DOI: 10.1259/bjr/69016171
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for Doppler ultrasound parameters of the thyroid in a healthy iodine-non-deficient population

Abstract: The aim of this study was to describe normal Doppler parameter values in the thyroid arteries in an iodine-replete region. 165 individuals were randomly selected in a community located in the south-east of Brazil. We obtained a clinical history on each subject and determined serum thyrotropin, antiperoxidase antibodies, thyrotropin receptor antibody (TRAb) and thyroid volumes through ultrasound. Subjects with thyroid disease and those under 20 years of age were excluded. 84 representative subjects (30 men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
2
16
2
1
Order By: Relevance
“…The possibility of increased VI (%) values in such subjects being an early sign of autoimmune thyroiditis remains hypothetical and needs to be addressed in a formal comparative prospective study. For our 34 healthy controls we found an overall mean VI equal to 3.55 %, similar to 3.67% found by Macedo TAA et al in 84 healthy subjects (22). Increased vascularity in thyroid sonography could be diagnosed in patients with TSH secreting pituitary adenomas or resistance to thyroid hormone (23), acromegaly (24), and pregnancy (25); however patients with such diseases were initially excluded and no related signs, symptoms or typical laboratory findings were detected in any of our healthy controls or any of the patients at the start or during the study.…”
Section: Discussionsupporting
confidence: 90%
“…The possibility of increased VI (%) values in such subjects being an early sign of autoimmune thyroiditis remains hypothetical and needs to be addressed in a formal comparative prospective study. For our 34 healthy controls we found an overall mean VI equal to 3.55 %, similar to 3.67% found by Macedo TAA et al in 84 healthy subjects (22). Increased vascularity in thyroid sonography could be diagnosed in patients with TSH secreting pituitary adenomas or resistance to thyroid hormone (23), acromegaly (24), and pregnancy (25); however patients with such diseases were initially excluded and no related signs, symptoms or typical laboratory findings were detected in any of our healthy controls or any of the patients at the start or during the study.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, there are significant differences in the degree of arterial flow between the superior and inferior thyroid arteries and between men and women. 27 In our study, we did not observe a difference in discordance between pairs of nodules involving lower pole only (45.5% discordance rate) and pairs of nodules between lower and nonlower poles (37.8%). Likewise, there were no significant differences in the rates of discordance based on sex.…”
Section: Discussioncontrasting
confidence: 63%
“…Uchida et al used the superior thyroid artery for measurements and reported a higher PSV in GD (78.48 ± 36.28 cm/s) compared to destructive thyrotoxicosis (52.39 ± 28.54 cm/s). For the inferior thyroid artery, a cutoff value of 40 cm/s for the PSV achieved differentiation of GD from thyroiditis with optimal diagnostic accuracy . A point to consider when analyzing cutoff values is to locate the vessel to be measured, as values differ among intrathyroidal vessels and inferior and superior thyroid arteries.…”
Section: Discussionmentioning
confidence: 99%